Keep Calm and Carry On: The Short- vs. Long-Run Effects of Mindfulness Meditation on (Academic) Performance - Lea Cassar; Mira Fischer; Vanessa Valero (Institute of Labor Economics (IZA), 2022)
Mindfulness-based meditation practices are becoming increasingly popular in Western societies, including in the business world and in education. While the scientific literature has largely documented the benefits of mindfulness meditation for mental health, little is still known about potential spillovers of these practices on other important life outcomes, such as performance. We address this question through a field experiment in an educational setting. We study the causal impact of mindfulness meditation on academic performance through a randomized evaluation of a well-known 8-week mindfulness meditation training delivered to university students on campus. As expected, the intervention improves students' mental health and non-cognitive skills. However, it takes time before students' performance can benefit from mindfulness meditation: we find that, if anything, the intervention marginally decreases average grades in the short run, i.e., during the exam period right after the end of the intervention, whereas it significantly increases academic performance, by about 0.4 standard deviations, in the long run (ca. 6 months after the end of intervention). We investigate the underlying mechanisms and discuss the implications of our results.
Keywords: I21; C93; I12; I31; 330; performance; mental health; education; meditation; field experiment